Timing of Initial Posttracheostomy Surveillance Endoscopy in Pediatric Patients. (March 2020) - Smith, Matthew M.; de Alarcon, Alessandro; Meinzen-Derr, Jareen; Cohen, Aliza P.; Born, Hayley; Wilcox, Lyndy J.; Benscoter, Dan T.; Hart, Catherine K.
Objective: To determine the optimal timing of the first posttracheostomy microlaryngoscopy and bronchoscopy (MLB). Study Design: Case series with chart review. Setting: Tertiary pediatric medical center. Subjects and Methods: Patients (<21 years of age) who underwent tracheostomy placement from January 1, 2011, to December 31, 2016. Patients were divided into early and late posttracheostomy surveillance groups (<6 weeks vs 6 to 14 weeks, respectively) based on the timing of their first posttracheostomy MLB. The primary outcome was to ascertain the clinical yield of the initial posttracheostomy MLB by documenting whether a medical or surgical treatment decision was made based on MLB findings. Results: In total, 202 patients were included; of these patients, 162 met criteria for placement in the early group and 40 met criteria for the late group. There was no significant difference between the early and late groups regarding whether a medical or surgical decision was made at the time of the first MLB (21.5% vs 19%, respectively; P = .49). Multiple logistic regression identified that the presence of tracheostomy-related symptoms prior to MLB (odds ratio, 6.75; 95% confidence interval, 2.78-16.39) was the sole predictor of a medical or surgical decision being made at the first posttracheostomy MLB. Conclusion: The presence of tracheostomy-related symptoms was predictive of a medical or surgical decision being made using information obtained at the time of the first posttracheostomy MLB. We thus recommend that surveillance endoscopy be initiated when tracheotomized children start to develop tracheostomy-related symptoms.